Dear DC super-villains - Northrop, Michael (DC graphic novels for kids, 2021)
"Peek inside the lives of DC's infamous rogues gallery, where curious kids write to notorious scoundrels, asking them about life on the dark side. Read between the lines and you may notice the baddies are up to something big! Will the Justice League show up in time to stop them?"--